Social Media Recruitment and Generation Z Job Application Intentions: The Mediating Effect of Employer Branding - Putry Aliyya Baasitha; Muhammad Mathori (Research Horizon, 2026)
The swift evolution of digital technology has transformed hiring methods, with Generation Z placing greater dependence on social media for job-related information. This research seeks to investigate how social media functions as a recruitment instrument on Generation Z’s willingness to seek employment and to explore the mediating influence of employer branding within this context. This study utilized a quantitative method through a survey approach by distributing questionnaires to participants identified as Generation Z. The sampling method employed was purposive sampling, involving a total of 100 respondents. The gathered data were assessed through Structural Equation Modeling utilizing the Partial Least Squares method. The findings show that using social media for recruitment positively and significantly influences Generation Z’s desire to seek employment. Moreover, employer branding positively impacts the intention to apply for jobs. The mediation analysis indicates that employer branding partially mediates the connection between social media recruitment and the job application intention of Generation Z. These results indicate that organizations need to refine their recruitment strategies via social media and cultivate a robust employer brand to improve their appeal to young job applicants.